Dispute settlement reports 2019. Volume IV, Pages 1745-2168 - World Trade Organization (Cambridge : Cambridge University Press, 2021)
These are the WTO's authorized and paginated reports in English. They are an essential addition to the library of all practising trade lawyers and a useful tool for students and academics worldwide working in the field of international economic or trade law. DSR 2019: Volume IV contains the Appellate Body report on 'United States - Measures Affecting Trade in Large Civil Aircraft (Second Complaint) (WT/DS353), Recourse to Article 21.5 of the DSU by the European Union'.
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: Foreign trade regulation -- Cases; Tariff -- Law and legislation -- Cases; Competition, Unfair -- Cases; Dispute resolution (Law) -- Cases